2019
DOI: 10.4028/www.scientific.net/jera.41.60
|View full text |Cite
|
Sign up to set email alerts
|

Signal Propagation and Analysis in Wireless Underground Sensor Networks

Abstract: The most challenging issue in the design of wireless sensor networks for the application of localization in the underground environment, mostly for miner’s location, is the sensor nodes’ energy consumption, efficiency and communication. Underground Wireless Sensor Networks are active and promising area of application of Wireless Sensor Networks (WSNs), whereby sensor nodes perform sensing duties in the underground environment. Most of the communication techniques used in the underground environment experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For the conceptual scheme in the radio frequency area, the coefficients are based on soil types. Zungeru et al [12] suggested a pulse power dependent on magnetic induction. Their analytical findings of the Magnetic Modulation derived the pulse strength with a usual electromagnetic field communication channel, an increase in signal-to-noise ratio, and fading channels of variance in node.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For the conceptual scheme in the radio frequency area, the coefficients are based on soil types. Zungeru et al [12] suggested a pulse power dependent on magnetic induction. Their analytical findings of the Magnetic Modulation derived the pulse strength with a usual electromagnetic field communication channel, an increase in signal-to-noise ratio, and fading channels of variance in node.…”
Section: Related Workmentioning
confidence: 99%
“…Eng way = {Eng way (wusn sn , wusn) Eng way (wusn sn , wusn x+1 ) Eng way (wusn way , SN)} (12) Ebl way is a set of variables for balancing load of Eng way .…”
Section: Based Transmission Path Selection In Wusnmentioning
confidence: 99%
“…RSSI Ranging. In indoor environments, the strength of wireless signals is unpredictable due to multipath propagation and shadowing effects, and log-distance models are often used to represent signal propagation losses [18]. Let the distance between the receiving node and the transmitting node be d, then the loss caused by the signal during propagation can be expressed as…”
Section: The Principle Of Rssi Rangingmentioning
confidence: 99%
“…Underground communication has recently gained considerable attention owing to its wide range of applications including seismic and climate change monitoring, smart agriculture, mining, infrastructure monitoring, industrial Internet of Underground Things (IoUT) and border patrol [1][2][3][4][5]. Existing well-established communication protocols for abovethe-ground communication cannot be directly modeled for underground communication because of the dynamic nature of the channel and the unpredictability of its characteristics such as temperature, humidity and composition, which directly influence signal propagation [2,3,6]. Consequently, many different communication techniques have been investigated, such as those involving electromagnetic (EM) waves [7], acoustic waves [8] and magnetic induction (MI) [9].…”
Section: Introductionmentioning
confidence: 99%